Is Janani Suraksha Yojana’s (JSY) Awareness A Reflection of Healthy Pregnancy Outcome? Differences In Rural Areas and Urban Slums - Sharma , Parul; Srivastava , Kajal; Vyas , Shaili; Kishore , Surekha; Semwal , Jayanti (National Journal of Community Medicine, 2012)
Context: Janani Suraksha Yojana (JSY), launched on 12th April,2005 under the umbrella of NRHM has shown it’s impact in terms of increase in number of institutional deliveries and decrease in maternal and neonatal mortality rates but still the awareness about the scheme is low in women from rural areas and urban slums, especially in low performing states. Aims: To assess the differences in awareness of married women from rural areas and urban slums regarding JSY and to study the effect of socio-demographic factors on the level of awareness. Settings and Design: A cross-sectional study was carried out in the rural areas and urban slums of field practice areas of Himalayan Institute of Medical Sciences, Dehradun, for a period of one year. Methods and Material: all the married women (15-49 years) of reproductive age group were included in the study. After taking informed consent from the head of the families and targets, the study subjects were interviewed by a pre-designed and pre-tested questionnaire. Statistical analysis used: SPSS 10 and Epi Info software (with Yate’s correction). Results: Awareness was more among women belonging to rural areas i.e 79%.Age, educational status, occupation, socio-economic status and place of residence showed a significant statistical association with the level of awareness. Conclusions: There is an urgent need to strengthen IEC campaigns and monitoring strategies.